Serum Bioavailable, Rather Than Total, 25‐hydroxyvitamin D Levels Are Associated With Hepatocellular Carcinoma Survival - Fang, Ai‐Ping; Long, Jing‐An; Zhang, Yao‐Jun; Liu, Zhao‐Yan; Li, Qi‐Jiong; Zhang, Dao‐Ming; Luo, Yun; Zhong, Rong‐Huan; Zhou, Zhong‐Guo; Xu, Yan‐Jun; Xu, Xiao‐Jun; Ling, Wen‐Hua; et al. (Hepatology (Baltimore, Md.), 2020)
Background and Aims Free and bioavailable 25‐hydroxyvitamin D (25OHD) are emerging measurements of vitamin D status. It remains unclear whether circulating free or bioavailable 25OHD are relevant to hepatocellular carcinoma (HCC) prognosis. Our aim was to test the hypothesis that bioavailable 25OHD may be a better serum biomarker of vitamin D status than total 25OHD on the association with HCC survival. Approach and Results We included 1,031 newly diagnosed, previously untreated patients with HCC from the Guangdong Liver Cancer Cohort enrolled between September 2013 and April 2017. Serum total 25OHD levels were measured using an electrochemiluminescence immunoassay. Serum‐free 25OHD levels were measured using a two‐step enzyme‐linked immunosorbent assay. Bioavailable 25OHD levels were calculated from measured free 25OHD and albumin using a previously validated equation. Primary outcomes were liver cancer–specific (LCSS) and overall survival (OS). Cox proportional hazards models were performed to calculate the multivariable hazard ratios (HRs) and 95% confidence intervals (CIs). During a median follow‐up of 726 days, 430 patients had deceased, including 393 deaths from HCC. In multivariable analyses, higher bioavailable 25OHD levels were significantly associated with better survival, independent of nonclinical and clinical prognostic factors including serum C‐reactive protein, Barcelona Clinic Liver Cancer stage, and cancer treatment. The multivariable‐adjusted HRs in the highest versus lowest quartile of bioavailable 25OHD levels were 0.69 (95% CI: 0.51, 0.93; P for trend = 0.014) for LCSS and 0.71 (95% CI: 0.53, 0.94; P for trend = 0.013) for OS. In contrast, neither total nor free 25OHD levels were associated with LCSS or OS. Conclusions Higher bioavailable, rather than total, 25OHD levels were independently associated with improved survival in a population‐based HCC cohort, suggesting a potential utility of bioavailable 25OHD in HCC prognosis.